Statistical item analysis of the physics examination for Center for Foundation studies (CFS) IIUM students using the Rasch model - Husin, Hafiz; Mohd Noor, Mazni; Mat Nawi, Mohd Nazir; Ishak, Izdihar (Centre of Foundation Studies, IIUM, 2021)
This study focuses on the statistical item analysis of the physics examination result for CFS students at the International Islamic University Malaysia (IIUM). In order to evaluate the quality of an item and the test as a whole, the Rasch Model is used in which simultaneously students' answers and test questions are studied. Twenty-three items were administered to 887 students taking Physics 1 during semester 1, 2020/2021 session. The Rasch model was used as an item analysis tool for the examination items. The test reliability was assessed with reliability indices after removing any misfit and outlier items that appear in the data. Item difficulties and examinee ability were measured and calculated by Rasch analysis at that point expressed into standard logit model and correct probability responses for the examination items. As a result, the estimated test reliability was 100% and person reliability was 83% respectively. The separation for the test item was estimated at 15.45 meanwhile, for the person was estimated at 2.52. The performance that is directly related to the students' weaknesses is obtained from the continuous assessments of the course, the end-ofsemester report analysis based on course outcomes and the item analysis. The results will be used as the basis for improving the teaching and learning process for this course.